Indole-3-Acetic Acid From Contaminant Fungus And Potential Application For Cell Cultures Of Alternanthera Sessilis - KARTHIKEYAN SUBBARAYAN; NITHYA VARADHARAJAN; RAJAGOPAL KALYANARAMAN (International Journal of Pharma and Bio Sciences, 2010)
Microbes use Indole 3-acetic acid (IAA) to interact with plants including phytostimulation and circumvention of basal plant defence mechanism. Fungal contamination is the most predominant in Alternanthera sessilis tissue culture than bacteria. Colletotrichum Sp. produced 25 mg/l of IAA in presence of tryptophan (400 mg/l) in Czapex medium. In vitro studies were performed to utilize the IAA for callus induction of A. sessilis, an important medicinal plant used in Siddha system of medicine. In Murashige and Skoog medium supplemented with 9.0 µM 2,4-D + 2.8 µM IAA, callus induction was maximum. Callus induction on 1.8 µM fungal IAA + 1.0 µM IAA (HiMedia) shows the potential application of fungal IAA in plant cell cultures.